Medialogues - Chen, Evelyn; Siya, Chen; Seah, Lianne; Wong, Patrick
SYMC 2005 was Singapore's inaugural conference providing a platform for the exchange of views and research about youth-related issues in mass media. It was organised by a team of final-year Mass Communication students from the School of Film & Media Studies (FMS), Ngee Ann Polytechnic. SYMC aims to encourage Singaporean youths to be active and engaged in issues that matter to them and to foster a conducive environment for youths to come together, network, and share ideas.